Methyl ester production from high free fatty acid content with Ce/Zeolite bifunctional catalyst - Aisyah Sabrina Nurul Syahidah; Dinanti Putrisia Wilujeng; W. Widayat; H. Hadiyanto; S. Sulardjaka; Noorzita Ngadi (Center of Biomass & Renewable Energy (CBIORE), 2026)
The production of methyl esters from high free fatty acid (FFA) feedstock remains a critical challenge in biodiesel processing, particularly when using Palm Acid Oil–waste cooking oil (PAO–WCO) with an initial FFA content of 53.21%. Such high FFA content significantly reduces reaction efficiency and necessitates a conventional two-step process involving esterification to lower the FFA level followed by transesterification to convert triglycerides into methyl esters. This multistep approach limits process efficiency and increases operational complexity for high-FFA feedstock. This study investigates the use of a bifunctional Ce/Zeolite catalyst to enable simultaneous esterification and transesterification in a single-step process for high FFA content oil. The zeolite support was synthesized from geothermal waste, and cerium was incorporated via impregnation. The catalyst was characterized using SEM–EDX, X-ray diffraction (XRD), and Brunauer–Emmett–Teller (BET) surface area analyses. The reaction was conducted under various operating conditions, including different temperatures and catalyst loadings. The Ce/Zeolite catalyst exhibited effective bifunctional activity, enhancing the simultaneous conversion of FFAs and triglycerides in high FFA content feedstock. The optimum conditions were a methanol-to-oil molar ratio of 12:1, 4 wt% catalyst loading, and a reaction temperature of 50 °C for 180 min. Under these conditions, FAME concentration of 91.5% was obtained, with FFA conversion of 25.31% (reduction of 13.47% FFAs from initial 53.21%) achieved in a single-step transesterification process. These results demonstrate that Ce/Zeolite is a promising bifunctional catalyst for the efficient processing of high FFA content oil, offering a simplified and more sustainable pathway for industrial biodiesel production.